Aerva lanata: A review on phytochemistry and pharmacological aspects - Goyal, Manoj; Pareek, Anil; Nagori, B. P.; Sasmal, D. (Pharmacognosy Reviews, 2011)
Aerva lanata (L.) A. L. Juss. ex Schultes. (Amaranthaceae) locally known as ‘bui’ is an erect or prostrate undershrub with a long tap-root and many wolly-tomentose branches, found in the wild, throughout India. In traditional medicine the plant is used in cough, strangury (slow to be and painful discharge of urine), headache and urolithiasis. The photochemical constituents present in the plant include alkaloids (ervine, methylervine, ervoside, aervine, methylaervine, aervoside, ervolanine, and aervolanine), fl avanoids (kaempferol, quercetin, isorhamnetin, persinol, persinosides A and B), methyl grevillate, lupeol, lupeol acetate benzoic acid, β-sitosteryl acetate and tannic acid. Pharmacological studies reported diuretic, anti-infl ammatory, hypoglycemic, anti-diabetic, antiparasitic, antimicrobial, hepoprotective, anti-urolithiasis, antiasthmatic, antifertility and hypolipidemic properties of Aerva lanata. This review article includes the detailed exploration of the morphology, phytochemistry, and pharmacological aspects of Aerva lanata in an attempt to provide a direction for further research.
Keywords: Aerva lanata; ervine; ervoside; methylervine